Hyperferritinemia: the link between COVID-19, inflammation, and patient comorbidities - Lazar, Angela Madalina (Journal of Ideas in Health, 2021)
Ferritin is a key molecule in iron metabolism, as it stores the iron in a non-toxic form for the cells. Serum ferritin is a parameter that reflects the iron content of the body. However, serum ferritin is also an acute-phase reactant protein, as increased levels of serum ferritin are reported in many diseases associated with inflammation. Hyperferritinemia was also reported in COVID-19 (the coronavirus disease 19) patients, where it is considered an independent prognostic factor for the patients, indicating increased severity of the disease, risk for complications, and death. Certain categories of patients (older, those with comorbidities) have an increased risk of SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) infectivity and developing more severe forms of COVID-19. Chronic/acute systemic inflammatory states often characterize such preexisting comorbidities. In the current paper, a new pathogenic link is proposed and analyzed: between preexisting hyperferritinemia in the context of patient comorbidities (metabolic, cardiovascular, kidney, inflammatory, autoimmune, cancer) and the risk of SARS-CoV-2 infectivity and of developing more severe forms of infection. Ferritin per se can be a causal agent in COVID-19, as it can generate and aggravate inflammation and contributes to the development of a severe cytokine storm. A severe, uncontrolled inflammatory state occurs, triggered by the high levels of serum ferritin, preexisting comorbidities, and SARS-CoV-2 infection, cause of lethality in many patients. The inflammatory stimuli can further aggravate the infection by activating ADAM-17 (disintegrin and metalloprotease 17), a key enzyme involved in ACE2 (angiotensin-converting enzyme 2) activation and viral infectivity. In this context, iron chelators and antioxidants could become potential lines of treatment in COVID-19.